Mycophenolate mofetil : fully utilizing its benefits for GvHD prophylaxis - Minagawa, Kentaro; Yamamori, Motohiro; Katayama, Yoshio; Matsui, Toshimitsu (International journal of hematology, 2012)
Mycophenolate mofetil (MMF) has been widely used for the prophylaxis of graft-versus-host disease (GvHD) in hematopoietic stem cell transplantation (HSCT), based on clinical evidence established in organ transplantations. MMF is not a cytotoxic, but rather a cytostatic agent, and there have been several reports of significant advantages in engraftment as well as greatly reduced stomatitis compared to methotrexate (MTX). MMF has been preferred for MTX-free immunosuppression, especially in reduced intensity conditioning, but it is suitable for GvHD prophylaxis for any type of HSCT. Some clinicians doubt its effectiveness, due to the lack of advantage over MTX in acute GvHD prophylaxis, especially in myeloablative conditioning. Pharmacokinetics studies of mycophenolic acid (MPA), the active form of MMF, show large inter- and intra-patient variation, which make interpretations of its clinical usefulness difficult. Nevertheless, several studies, including ours, have demonstrated that relatively higher area under the curve (AUC) of the MPA group leads to significant suppression of acute GvHD in prophylactic use. We propose a model algorithm for optimal dose finding using therapeutic drug monitoring (TDM) for MPA. Preemptive strategies depending on plasma MPA levels could yield more effective approaches to GvHD prophylaxis, alternative to MTX.